A Statistical Analysis of Building Information Modelling for PSC Bridge: Exploring the Role of Project Managers in Building Information Modelling for PSC Bridge (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Building Information Modeling (BIM) is nowadays becoming an effective method in the Indian as well worldwide in the sector of construction. Although of its short history, advanced growth took place in last dec-ade in BIM. This happened primarily due to its potential to handle construction projects. BIM creates a common gateway for coordination between various parties involved and system divisions on a particular project so as to shape them into an integrated team. The targets of BIM matches with IDPS (integrated pro-ject delivery system). The different branches are connected by BIM like effective communication, analyzes the project systems for effective implementation in construction, estimation of the cost and time of projects most of the time using quantity take-offs, sketches a gross idea of projects using visualization and building teams executing project. These are the things in different extents most of the times done by a project manager in different stages of the project.This paper targets to exhibit the suitability of BIM and role of project manager in the majority construction projects. Hence the importance of proper knowledge of BIM and experience of project managers for the success is highlighted. The requirements of thorough knowledge of BIM and valuable experience of project managers are simultaneously concentrated in this paper.